Utilizing a digital cohort to understand the health burden and lifestyle characteristics across the life course in individuals with polycystic ovary syndrome and possible PCOS - Peebles, Elizabeth; Wang, Zifan; Dracup, Erin; Sarcione, Carrie; Curry, Christine L.; Abrams, Kayley; Onnela, Jukka-Pekka; Williams, Michelle A.; Hauser, Russ; Coull, Brent; Mahalingaiah, Shruthi (Frontiers in Endocrinology, 2025)
IntroductionPolycystic ovary syndrome (PCOS) is an ovulation disorder associated with multiple health conditions. This study analyzed health and lifestyle characteristics of those with diagnosed and possible PCOS in a large, digital cohort.MethodsWe analyzed data from female participants who enrolled in the Apple Women’s Health Study-a mobile-application-based cohort in the United States and provided informed consent from 11/14/2019–12/14/2024. Specific analyses were further restricted to those who responded to relevant survey questions. Self-reported sociodemographic, health (conditions and age at diagnosis), and lifestyle characteristics were evaluated, stratified by PCOS status: PCOS (self-reported physician diagnosed PCOS), possible PCOS (self-reported irregular menses and androgen excess), and no PCOS. Among those with PCOS/possible PCOS, we further evaluated potential predictors of not reporting a PCOS diagnosis using multivariable logistic regression.ResultsOf participants providing medical history at enrollment, 12.6% (n=11,022) reported PCOS, and among the subset without a PCOS diagnosis and with relevant survey data, 17.4% (n=7,152) were assigned possible PCOS. The median baseline age was 35 years. Most participants self-identified as non-Hispanic White (74.2%). The possible PCOS group was slightly less educated (≤high school: possible PCOS 14.5%, PCOS 17.3%, no PCOS 14.0%). The PCOS/possible PCOS groups reported lower socioeconomic status (SES) than the no PCOS group (low SES: PCOS 32.7%, possible PCOS 31.6%, no PCOS 23.5%). The PCOS and possible PCOS groups displayed a high burden of disease (cardiometabolic, endometrial hyperplasia/cancer, pregnancy complications, mental health conditions). Compared to those without PCOS, those with PCOS reported less healthy lifestyle behaviors relevant to physical activity/sleep/stress/smoking and more healthy lifestyle behaviors relevant to alcohol intake/diet. The age at diagnosis for multiple health conditions was earlier for participants with PCOS compared to those without PCOS. Young/old age (18 - 29/40–50 years), lower educational attainment, lower SES, and lower BMI were positive predictors of not reporting a PCOS diagnosis.ConclusionsThis study demonstrated significant differences in health and lifestyle characteristics across PCOS status (PCOS, possible PCOS, no PCOS), identifying populations that could benefit from early risk reduction counseling. Our results may inform discussions around clinical care models through improving awareness of health predictors and lifestyle interventions.